Development of a self-sufficient Ad Hoc Sensor to Perform Electrical impedance tomography measurements from within imaged space - Abbas Ibrahim Mbulwa; Ali Chekima; Jamal Ahmad Dargham; Yew, Hoe Tung; Chin, Renee,Ka Yin; Wong, Wei Kitt (Springer Nature Singapore Pte Ltd., 2020)
Electrical Impedance Tomography (EIT) is an ill-posed problem whereby there are insufficient measured data to solve for a large amount of unknowns (finite elements). Conventionally, EIT measurements are performed on the boundary of an object or a process vessel. This results in a lower spatial resolution in central regions far off the conventional periphery electrodes. This paper presents the development of a self-sufficient EIT sensor with an aim to obtain EIT measurements from any locality within the object or the process vessel. An ad hoc EIT sensor that performs the current injection and voltage measurement around two pairs of electrodes is developed. The sensor consists of a current source, voltage amplifier, multiplexers, and microcontroller. Tests were conducted on a phantom tank. The sensor successfully performs localized voltage measurements from the interior of the imaged space with channel SNR average of 15dB.